New Emerging Issues and Wild Cards as Future Shakers and Shapers - Victor van Rij (Foresight and STI Governance)
From 2007 to 2010, the EC funded a series of blue sky projects on foresight, including on new methodologies for horizon scanning in several European countries. The projects resulted in the evaluation of current methods for obtaining and processing scanning data and  new conceptual thinking that may bridge the gap between scanning activities and policy-making. This paper provides an overview of conceptual thinking in two projects, SESTI and FAR Horizon. The key thinking is about  emerging issues and about imaginative or potential wild cards, both considered to be potential storylines for future development or events that require policy action. Storylines come close to the concept of future narratives, as used in the policy discourse regarding aging in the Netherlands. The  shows that narratives are used by policymakers when they fit a particular strategy, but that the narratives must compete with both present-day (experienced “past reality”) and future stories in policy discourse. The author describes strong “future” narratives and gives special attention those that include imaginative wild cards. The communicative strength of a future narrative (and the included issue) is decisive for its uptake in the discourse (in policy and business communities). However, this strength is only partly connected to its scientific or factual evidence base, since it may contain many elements that are not rational to make it strong.